Apoptosis levels in bovine Johne's disease ileal lesions and association with bacterial numbers. Issue 6 (November 2021) - Lucena, Amalia Naranjo-; Garza-Cuartero, Laura; McAloon, Conor; Mulcahy, Grace; Zintl, Annetta; Perez, José; Wolfe, Alan
Johne's disease (JD) is a chronic granulomatous enteritis caused by Mycobacterium avium subsp. paratuberculosis (MAP). While it is generally accepted that MAP employs immune subversion mechanisms, aspects of the host-pathogen relationship are not fully understood. We sampled 3 ileal tissue sections from 17 naturally infected cattle ( n = 51 sections) to analyze differences in cell types, apoptosis, and phagocytic cells. Diffuse multibacillary (DM) was the most common lesion type ( n = 17) followed by diffuse intermediate (DI; n = 15). DM lesions had significantly greater proportion of Treg cells (CD3 + FoxP3 +) relative to all CD3 + T cells as compared to DI forms ( P < .05). CD68 + individual cell size was significantly smaller in DM than in diffuse lymphocytic (DL) forms ( P < .05). Area of caspase-3 positivity (apoptosis) was greater in DM lesions than DL ( P < .05) and DI ( P < .0001), and was linked to higher numbers of MAP within the macrophage.